DETERMINATION OF THE GLASS TRANSITION TEMPERATURE OF METHACRYLATE COPOLYMERS - Nurlybayeva Аisha,; Rustem Ergali,; Seitbekova Gulnazia,; Sholak Abdugali,; Kalmakhanova Marzhan,; Akbolatova Symbat,; Edilbaeva Aigul, (Academic Scientific Journal of Chemistry, 2020)
We have obtained a new synthetic copolymers based on methyl methacrylate (MMA) and butyl methacrylate (BMA), with use of the dinitrile as an initiator of Azobisisobutyronitrile acid (AIBN). Hence, the obtained results show the important role of the structure of the polymer melt at a specific temperature or heat resistance intensive degradation of polymeric materials and other characteristics of the TGA. Heat resistance, as well as a certain temperature loss of the samples depends on the chemical structure of polymers, expressed in terms of the glass transition temperature, the compactness of the macromolecular coil in the copolymer, which is also determined by the structure of the coil. The role of the latter in determining the thermal resistance decreases as the glass transition temperature of the copolymer. It was found that the thermal degradation of butyl methacrylate copolymers studied by the mechanism of copolymerization and decomposition side butyl substituent.